3D discrete fracture network modelling of multiphysical processes in fractured media: recent advances and future prospects - Lei, Qinghua (Frontiers in Built Environment, 2025)
This Mini Review provides a focused and up-to-date summary of recent advancements in 3D discrete fracture network (DFN) modelling for simulating coupled thermo-hydro-mechanical-chemical processes in fractured rocks, which are crucial for various geotechnical engineering-related challenges. Particular emphasis is placed on recent developments in 3D DFN modelling technologies, which have enabled more realistic and detailed representations of fracture topologies, interactions, and multiphysics couplings. We highlight key advances in simulating complex multiphysical processes and phenomena in 3D fractured geological media such as flow channelling, stress fluctuation, fracture interaction, and anomalous transport. Despite these advances, significant challenges remain—especially in multiscale representation, mesh generation, model calibration, computational efficiency, and integration with field observational data. The review concludes by identifying current research gaps and proposing future directions aimed at enhancing model realism, advancing the simulation of multiscale multiphysical processes, and expanding the applicability of DFN models to real-world geological and geotechnical engineering challenges.